2017
DOI: 10.1113/jp274970
|View full text |Cite
|
Sign up to set email alerts
|

Chronic β2‐adrenoceptor agonist treatment alters muscle proteome and functional adaptations induced by high intensity training in young men

Abstract: Although the effects of training have been studied for decades, data on muscle proteome signature remodelling induced by high intensity training in relation to functional changes in humans remains incomplete. Likewise, β -agonists are frequently used to counteract exercise-induced bronchoconstriction, but the effects β -agonist treatment on muscle remodelling and adaptations to training are unknown. In a placebo-controlled parallel study, we randomly assigned 21 trained men to 4 weeks of high intensity trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
73
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(86 citation statements)
references
References 100 publications
(134 reference statements)
12
73
0
Order By: Relevance
“…Because basal metabolic rate is related to total mass of predominantly lean tissues (eg, skeletal muscle), trueV˙O 2 ‐reserve and trueV˙O 2max relative to body mass are more sensitive to changes in aerobic capacity than absolute trueV˙O 2max . Partly consistent with the present findings, we previously observed that 4 weeks of endurance training, with daily terbutaline treatment in a similar dose, abolished training‐induced improvements in trueV˙O 2max and iPPO compared with placebo . In contrast, Dickinson et al observed no effect of daily treatment of beta 2 ‐adrenergic agonist salbutamol (1.6 mg daily) on trueV˙O 2max in recreationally active individuals following a 6‐week period with concurrent resistance and endurance training.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Because basal metabolic rate is related to total mass of predominantly lean tissues (eg, skeletal muscle), trueV˙O 2 ‐reserve and trueV˙O 2max relative to body mass are more sensitive to changes in aerobic capacity than absolute trueV˙O 2max . Partly consistent with the present findings, we previously observed that 4 weeks of endurance training, with daily terbutaline treatment in a similar dose, abolished training‐induced improvements in trueV˙O 2max and iPPO compared with placebo . In contrast, Dickinson et al observed no effect of daily treatment of beta 2 ‐adrenergic agonist salbutamol (1.6 mg daily) on trueV˙O 2max in recreationally active individuals following a 6‐week period with concurrent resistance and endurance training.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, terbutaline treatment caused a non‐significant decline in the content of IDH, the rate‐limiting enzyme in the Krebs cycle . This indicates similar detrimental effects on oxidative enzymes as observed in a similar population . In contrast, the content of HAD, an important enzyme in the process of mitochondrial beta‐oxidation, did not change which is in accordance with Hostrup et al who showed that 4 weeks of supratherapeutic terbutaline administration did not affect content of HAD.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations